Pathophysiology, Diagnosis and Treatment of Somatosensory Tinnitus: A Scoping Review - Haider, Haúla F.; Hoare, Derek J.; Costa, Raquel F. P.; Potgieter, Iskra; Kikidis, Dimitris; Lapira, Alec; Nikitas, Christos; Caria, Helena; Cunha, Nuno T.; Paço, João C. (Frontiers in Neuroscience, 2017)
Somatosensory tinnitus is a generally agreed subtype of tinnitus that is associated with activation of the somatosensory, somatomotor, and visual-motor systems. A key characteristic of somatosensory tinnitus is that is modulated by physical contact or movement. Although it seems common, its pathophysiology, assessment and treatment are not well defined. We present a scoping review on the pathophysiology, diagnosis, and treatment of somatosensory tinnitus, and identify priority directions for further research. Methods Literature searches were conducted in Google Scholar, PubMed and EMBASE databases. Additional broad hand searches were conducted with the additional terms etiology, diagnose, treatment. Results Most evidence on the pathophysiology of somatosensory tinnitus suggests that somatic modulations are the result of altered or cross-modal synaptic activity within the dorsal cochlear nucleus or between the auditory nervous system and other sensory subsystems of central nervous system (e. g. visual or tactile). Presentations of somatosensory tinnitus are varied and evidence for the various approaches to treatment promising but limited. Discussion and conclusions Despite the apparent prevalence of somatosensory tinnitus its underlying neural processes are still not well understood. Necessary involvement of multidisciplinary teams in its diagnosis and treatment has led to a large heterogeneity of approaches whereby tinnitus improvement is often only a secondary effect. Hence there are no evidence-based clinical guidelines, and patient care is empirical rather than research-evidence-based. Somatic testing should receive further attention considering the breath of evidence on the ability of patients to modulate their tinnitus through manouvers. Specific questions for further research and review are indicated.